Self-Esteem among Malay Children of Parents with Schizophrenia in Kelantan, Malaysia - Che Yusoff, Nor Azwani; Othman, Zahiruddin; Husain, Maruzairi; Jaapar, Sharifah Zubaidiah Syed; Yasin, Mohd Azhar Mohd; Yaacob, Mohd Jamil (Japan International Cultural Exchange Foundation, 2016)
Background: Studies have demonstrated that children of parents with schizophrenia have low self-esteem. However, only scant data exist for the local population. Objectives: The objective of this study was to evaluate self-esteem of Malay children of parents with schizophrenia and to determine the associated socio-demographic and clinical factors. Methods: A total of 118 children of parents with schizophrenia who attended Hospital Universiti Sains Malaysia (HUSM) between May-September 2012 participated in the study. The children's self-esteem was measured using the Malay version of Rosenberg self-esteem scale (RSES). Patient's psychopathology and level of functioning were measured using the positive and negative syndrome scale (PANSS) and global assessment of functioning (GAF), respectively. Results: The RSES mean score was 23.86 ± 5.31 and low self-esteem (RSES score < 20) was reported by 32.2% subjects. In multivariate analysis, the independent factors associated with low self-esteem were girls (OR 6.29), poor academic achievement (OR 5.49), school attendance/ stopped schooling (OR 9.43), awareness of parental mental illness (OR 5.12) and parent was divorced/widow/separated (OR 3.56). Psychopathology and level of functioning of parents were not significantly associated with self-esteem of the children. Conclusion: Malay children, particularly girls, of parents with schizophrenia had low self-esteem. Children with school problems and whose parents divorced/separated also had low self-esteem.